Role of Digitalization after Demonetization in Economy - Chouhan, N; Rathore, D; Chhabra, I (International Journal of Computer Sciences and Engineering, 2025)
The research paper presents that how the demonetization impact on digital India. In the world of technology the demonetization helps to take step towards the far growing technology as well as in rural areas people used to do payment with the help of e-wallet, mobile payment and it helps to grow society and economy of India. The demonetization also helps in reducing the black money and the decision was taken when the black money was increased a lot and through demonetization it overcomes the black money. The paper also discusses the economic impact of demonetization on digitalization and gives suggestion to improve the digitalization in India.